Functional integration of the histone acetyltransferase MOF into the dosage compensation complex. - Morales, V.; Straub, T.; Neumann, M.F.; Mengus, G.; Akhtar, A.; Becker, P.B. (The EMBO Journal, 2004)
Dosage compensation in flies involves doubling the transcription of genes on the single male X chromosome to match the combined expression level of the two female X chromosomes. Crucial for this activation is the acetylation of histone H4 by the histone acetyltransferase (HAT) MOF. In male cells, MOF resides in a complex (dosage compensation complex, DCC) with MSL proteins and noncoding roX RNA. Previous studies suggested that MOF's localization to the X chromosome was largely RNA-mediated. We now found that contact of the MOF chromo-related domain with roX RNA plays only a minor role in correct targeting to the X chromosome in vivo. Instead, a strong, direct interaction between a conserved MSL1 domain and a zinc finger within MOF's HAT domain is crucial. The functional consequences of this interaction were studied in vitro. Simultaneous contact of MOF with MSL1 and MSL3 led to its recruitment to chromatin, a dramatic stimulation of HAT activity and to improved substrate specificity. Activation of MOF's HAT activity upon integration into the DCC may serve to restrict the critical histone modification to the male X chromosome.